2011
DOI: 10.1002/lt.22415
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide induces hypothermia tolerance in Kupffer cells and attenuates liver ischemia/reperfusion injury in rats

Abstract: Ischemia/reperfusion (I/R) injury in liver grafts, initiated by cold preservation and augmented by reperfusion, is a major problem complicating graft quality, post-transplant patient care, and outcomes of liver transplantation (LTx). Kupffer cells (KC) play important roles in I/R injury; however, little is known about their changes during cold preservation. We examined whether pretreatment with carbon monoxide (CO), a cytoprotective product of heme degradation, would influence KC activity during cold storage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…Based on fundamental thermodynamic principles of enzyme action, it would be expected that lower body temperatures could significantly decrease the enzyme catalyzed reaction rates for production of reactive oxygen and nitrogen species. Experimental evidence in support of this expectation has been reported in the form of inhibition of TNF-α and nitric oxide production in hypothermic rats [9]. Thus, direct temperature-dependent decreases in activity of enzymes that produce antimicrobial agents could explain a portion of the effects of SMD on delayed clearance of bacteria noted in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Based on fundamental thermodynamic principles of enzyme action, it would be expected that lower body temperatures could significantly decrease the enzyme catalyzed reaction rates for production of reactive oxygen and nitrogen species. Experimental evidence in support of this expectation has been reported in the form of inhibition of TNF-α and nitric oxide production in hypothermic rats [9]. Thus, direct temperature-dependent decreases in activity of enzymes that produce antimicrobial agents could explain a portion of the effects of SMD on delayed clearance of bacteria noted in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study, it was reported that CO inhalation ameliorated hepatic ischemia reperfusion injury by the suppression of Kupffer cell activation in a transplant-induced hepatic ishemia reperfusion rat model [13]. Furthermore, a previous in vitro study showed that ROS generation by Kupffer cells under hypothermic conditions was inhibited by a pre-exposure to CO [14]. In the present study, it was observed that CO-RBC resuscitation suppressed ROS production by activated Kupffer cells at 1 hr after hemorrhage and resuscitation (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, toll-like receptor-4 (TLR-4) activation on active Kupffer cells by a response to high mobility group box-1 (HMGB-1) is thought to be crucial in producing inflammatory cytokines in the case of ischemia reperfusion [12]. Previous in vitro and in vivo studies have shown that CO inhibits the generation of ROS and inflammatory responses by Kupffer cells [13,14]. Taking the above evidence into consideration, we hypothesize that CO-RBC inhibits the reduction of hepatic CYP content induced by hemorrhage and resuscitation by suppressing Kupffer cell activation and, thus, the suppression of ROS production and the expression of cytokines via the HMGB-1/ TLR-4 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…An additional mechanism for CO-mediated protection during lung I/R involves downregulation of the pro-inflammatory transcription factor Egr-1 [32]. Several studies demonstrated that pretreatment with CO donor compounds can ameliorate liver transplant-associated I/R injury through increased hepatic HSP70 expression [39], and suppression of inflammatory responses via downregulation of the MEK/ERK1/2 signaling pathways [40]. Hepatic I/R injury can be attributed to the infiltration of immune cells and to apoptosis of liver cells.…”
Section: Discussionmentioning
confidence: 98%